(untitled) (World Bulletin of Public Health, 2024)
The growth of secondary immunodeficiency in the population and the increasing role of atypical pathogens against this background have set new challenges for doctors and researchers. Against this background, pneumonia becomes severe and protracted. Diagnosis of atypical pathogens such as Chlamydophila pneumoniae, Mycoplasma pneumoniae (M. pneumoniae), Legionella pneumophila is particularly difficult. Currently, there are no uniform standards for the diagnosis of these pathogens, and the available data are only advisory in nature.